Extracellular Vesicles of Stem Cells to Prevent BRONJ. (May 2020) - Watanabe, J.; Sakai, K.; Urata, Y.; Toyama, N.; Nakamichi, E.; Hibi, H.
Extracellular vesicles (EVs), several tens to hundreds of nanometers in size, are vesicles secreted by cells for intercellular communication. EVs released from mesenchymal stem cells (MSC-EVs) have the potential to treat multiple diseases. This study aimed to determine the effects of MSC-EVs on bisphosphonate-related osteonecrosis of the jaw (BRONJ), whose pathogenesis and treatment are not yet established. To this end, zoledronic acid (ZOL) was administered to bone marrow cells and fibroblasts in vitro. In vivo, a BRONJ model was produced by administering ZOL to rats and extracting teeth. Each MSC-EV-treated and nontreated group was compared histologically and molecularly. In vitro, the nontreated group showed an increased number of β-galactosidase-positive cells and expression of senescence-associated genes p21, pRB and senescence-related inflammatory cytokines. Conversely, MSC-EV administration decreased the number of senescent cells and expression levels of p21, pRB and inflammatory cytokines. In vivo, in the nontreated group, the socket was partially uncovered by the oral epithelium, leaving an exposed bone. Conversely, in the MSC-EV-treated group, the socket was healed. Besides, in the nontreated group, β-galactosidase-positive cells existed in the socket and colocalized with the CD90 and periostin-positive cells. However, there were few β-galactosidase-positive cells in the MSC-EV-treated group. Furthermore, gene expression of stem cell markers Bmi1 and Hmga2 and the vascular endothelial marker VEGF was significantly increased in the MSC-EV-treated group, compared with that in the nontreated group. These results indicate that MSC-EVs prevent ZOL-induced senescence in stem cells, osteoblasts, and fibroblasts and reduce inflammatory cytokines. Furthermore, administration of MSC-EVs prevented senescence of cells involved in wound healing and the spread of chronic inflammation around senescent cells, thereby promoting angiogenesis and bone regeneration and preventing BRONJ.